Legal regulation of smart contracts - Askarbekova, А.; Niyazovа, А.Н.; Abdrassulova, А.Е. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article considers some aspects of legal regulation of smart contracts, which are becoming more and more relevant with the development of information technologies. The legislation and legal experience of foreign countries on conclusion and execution of "smart contracts" are studied in detail. As is known, currently there are several ways of integrating smart contract into transactions. The most relevant model of smart contract conclusion is the mixed model, the positive sides of using this form are analysed in the relevant provisions of the article. In its turn, the very legal nature of this type of contracts causes lively disputes in the civilistic environment, which is demonstrated by various opinions given in the article on the topic under consideration. There is no doubt that the widespread development of smart contracts in the near future can significantly help to reduce risks for the parties to the contract, exclude unscrupulous performers and suppliers from the market, as well as show a number of other advantages.